2011
DOI: 10.1097/ccm.0b013e31821b843b
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem responses can predict death and delirium in sedated patients in intensive care unit*

Abstract: Assessment of brainstem responses is feasible in sedated critically ill patients and loss of selected responses is predictive of mortality and altered mental status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 30 publications
3
41
0
1
Order By: Relevance
“…Coma was defined as GCS <8 in non-sedated patients or after 3 days of discontinuation of sedation in previously sedated patients [15]. Seizures were defined as generalized or focal (face or limb) tonic or clonic movement or recurrent twitching of one limb or eyelid twitching.…”
Section: Methodsmentioning
confidence: 99%
“…Coma was defined as GCS <8 in non-sedated patients or after 3 days of discontinuation of sedation in previously sedated patients [15]. Seizures were defined as generalized or focal (face or limb) tonic or clonic movement or recurrent twitching of one limb or eyelid twitching.…”
Section: Methodsmentioning
confidence: 99%
“…Of the set of brainstem reflexes tested upon admission, we found that the abolition of corneal reflexes was most predictive of BD, and that its predictive value did not differ according to whether the ICH was infratentorial. Sharshar et al [43] recently reported the neurological examination of sedated (by midazolam with or without sufentanil) patients admitted to the ICU without neurological disease [43]; corneal reflexes were abolished in <10% of sedated patients, and other brainstem reflexes were abolished in 20-50% of them [43]. Considering that 61% of our patients had received midazolam with or without sufentanil before admission to the ICU, we speculate that the minor effect of these sedatives on the corneal reflexes may explain why the abolition of these reflexes was the variable most predictive of BD.…”
Section: Discussionmentioning
confidence: 99%
“…The FOUR score adds an additional layer of sophistication to the assessment of coma by scoring brainstem reflexes in addition to the classical eye, motor and verbal responses elicited spontaneously or in response to a nociceptive stimuli. For example, an absent cough reflex is associated with 28‐day mortality in sedated critically ill patients [17]. …”
Section: Syndromesmentioning
confidence: 99%
“…Brainstem dysfunction might result in impaired alertness and impaired cardiovascular and immune controls, thereby leading to increased mortality. We found that the early abolition of the cough reflex and oculocephalogyric response was independently associated with increased ICU mortality in sedated critically ill patients [17]. Decreased heart rate variability, reflecting an impaired sympathetic activity originating from the brainstem autonomic centers, is also associated with a worse outcome in sepsis [30].…”
Section: Structuresmentioning
confidence: 99%